IMPROVING STUDENTS’ READING COMPREHENSION THROUGH INDONESIAN FOLKTALE AT EIGHT GRADE OF SMP NEGERI 2 DONDO - Mohammad Rafi'i (Jurnal Madako Education, 2017)
The objective of this research is to find out whether Indonesian Folktale can improve students’ reading comprehension  or not. This research is pre experimental research design consist of one group pre-test and post-test. The Population of this research are the eight grade of SMP Negeri 2 Dondo in 2016/2017 academic year. The sample of this research is selected by using purposive sampling technique and the selected class is VIIIb consisted of 29 students. In collecting the data, the researcher conduct test covered pre and post test. The researcher analized the data statically.The result of the test showed that the students’ mean score in posttest 74.83 is higher than pretest 33.38. To know the significant difference between pretest and posttest, the researcher compared the value of t-counted and t-table by applying 0.05 level of significance for two-tailed test with 28 degree of freedom (29-1=28), the researcher found that the t – table is 2.048. It means that the t-counted (23.96) is higher than t-table (2.048) and the hypothesis of this research is accepted.The researcher concluded that using Indonesian Folktale can improve students’ reading comprehension at eight grade of SMP Negeri 2 Dondo.Key Word: Reading comprehension, Indonesian Folktale.